Inequality, exclusion and civil war - Buhaug, Halvard; Cederman, Lars-Erik; Gleditsch, Kristian (Politica, 2016)
Much of the recent research on civil war treats explanations rooted in political and economic grievances with considerable suspicion and claims that there is little empirical evidence of any relationship between ethnicity or inequality and political violence. We argue that common indicators used in previous research fail to capture fundamental aspects of political exclusion and economic inequality that can motivate conflict. Through a statistical analysis of all civil wars since 1960, we show that our theoretically informed indicators of political discrimination and economic marginalization among ethnic groups are powerful predictors of civil war onset. Individual-based inequality indicators, in contrast, display only weak effects. This article in Norwegian is a revised and updated version of earlier work published in English.